Penyuluhan Menyikapi Efek Media Sosial Terhadap Perubahan Sosial Masyarakat Dusun I Desa Kampung Baru Kabupaten Labuhanbatu - Indah Roja Junaidi; Pristiyono Pristiyono; Abdul Halim (Jurnal Pengabdian UNDIKMA, 2022)
The purpose of this community service is to provide informal counseling and provide positive and useful education about how to respond to the use of social media rationally and wisely while at the same time providing negative examples of the misuse of social media in social life for the people of Dusun 1, Kampung Baru Village, West Bilah District, Labuhanbatu Regency. This community service is carried out using outreach methods with the target of communicating face-to-face with the community. The evaluation instrument for this activity uses tests (subjective & objective through quizzes, oral and written questions, etc.) and non-tests (interviews, questionnaires, observations, etc.) and is analyzed descriptively. The results of this community service counseling were carried out during the covid-19 period where almost all residents who took part in this activity had received stage I vaccination so that they had met the requirements for the covid-19 prokes. The level of understanding of using social media is considered quite good, this can be seen from the lack of reports received by the village government on the misuse of social media in social life. There is an active role as well as residents and village governments in educating the community regarding the use of social media to assist and monitor the use of social media for residents. Inviting citizens to use social media to gain profits by marketing their businesses to social media as a form of socialization of digitalization marketing.